Evaluación de medios de cultivo para la Micropropagación In vitro de Orquídeas de las especies Cattleya spp. Y Oncidium lanceanum en Tarapoto - Padilla Gómez, Engels Darwin (2008)
This work was executed in the Plant Tissue Culture Laboratory at the National University of San Martín - Tarapoto. Its objective was assay five different culture media for in vitro gennination and development In Peruvian orchids Cattleya spp. and Oncidium lanceanum, they were sown from seeds using the green pod method and the statistical used was an ANOVA In a completely randomized design with five treatments and ten repeats each. Seeds started germination and protocom development 30 days after sowing in a germination culture media, with a very low levels of contamination, recorded after two weeks after sowing, because the aseptic conditions at replating from germination to development and rooting culture media. 24 weeks after sowing in culture medium for development and rooting (Phase 11), plantlets developed, in average values: 04 leaves for Cattleya spp. and 4,5 leaves for Oncidium lanceanum, with 12.00mm high for Cattleya spp., 28.3mm for Oncidium lanceanum; 2.5 roots in Cattleya spp. And 2.9 roots for Oncidium Janceanum. These data belong to Treatment 04, the treatment with best results for the whole process of orchid propagation in vitro. Costs of production for every culture media used (five treatments) was determined. In the same way, costs of production for a plantlet produced under in vitro conditions were determined. These data shown a noticeable reduction in costs when using banana homogenated and coconut milk (Treatment 04) as culture media components .